Tectonic compaction shortening in toe region of isolated listric normal fault, North Taranaki Basin, New Zealand - Chris K. Morley (2018)
© 2016 The Authors. Basin Research © 2016 John Wiley & Sons Ltd, European Association of Geoscientists & Engineers and International Association of Sedimentologists. Industry 2D and 3D seismic data across the North Taranaki Basin displays two listric normal faults that formed during Pliocene shelf edge clinoform progradation. The faults die out in the down-transport direction with no evidence for contractional structures, except for two small thrust faults in one narrow zone. When active, the detachments lay at depths of about 1000 m below the seafloor. The overlying section had high initial porosities (30–60%). It is estimated that loss of about 17–20% pore volume by lateral compaction, and fluid expulsion over a distance of about 4–6 km in the transport direction occurred in place of folding and thrusting. Seismic and well evidence for abnormally highly compacted shales suggests there is about 6% less porosity than expected for in the prekinematic section, which possibly represents a residual of the porosity anomaly caused by lateral compaction. The observations indicate significant shortening (~20%) by lateral compaction and probably some layer parallel thickening are important deformation mechanisms in near-surface deepwater sediments that needs to be incorporated into shortening estimates and ‘balanced’ cross-sections. A key factor in listric fault initiation near the base of slope is inferred to be transient, increased pore fluid pressure due to lateral expulsion of fluids from beneath the prograding Giant Foresets Formation.